Synchronization Control for Stochastic Neural Networks with Mixed Time-Varying Delays - Qing Zhu; Aiguo Song; Shumin Fei; Yuequan Yang; Zhiqiang Cao (The Scientific World Journal)
Synchronization control of stochastic neural networks with time-varying discrete and continuous delays has been investigated. A novel control scheme is proposed using the Lyapunov functional method and linear matrix inequality (LMI) approach. Sufficient conditions have been derived to ensure the global asymptotical mean-square stability for the error system, and thus the drive system synchronizes with the response system. Also, the control gain matrix can be obtained. With these effective methods, synchronization can be achieved. Simulation results are presented to show the effectiveness of the theoretical results.